HUBUNGAN TINGKAT KESEPIAN DENGAN KUALITAS HIDUP PADA LANSIA DI PANTI WERDHA PUCANG GADING SEMARANG DAN WENING WARDOYO UNGARAN: HUBUNGAN TINGKAT KESEPIAN DENGAN KUALITAS HIDUP PADA LANSIA DI PANTI WERDHA PUCANG GADING SEMARANG DAN WENING WARDOYO UNGARAN - Setiyowati, Fenny; Luthfa, Iskim; Abrori, Abrori (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2025)
Background: Elderly is the final stage of life. In this process, the elderly will experience a decline in various aspects of their body function. One of the factors experienced by the elderly is psychological problems in the form of feelings of loneliness. Feelings of loneliness in the elderly will certainly have an impact on the quality of life of the elderly. One of the benchmarks used to assess the welfare of the elderly is the quality of life. Therefore, a harmonious relationship with family, friends, and the environment is very important to improve the quality of life of the elderly positively. Objective: This study aims to determine the relationship between the level of loneliness and the quality of life in the elderly in nursing homes. Methods: . This study uses a cross-sectional methodology and is quantitative. Data were collected using the loneliness scale from UCLA Loneliness and quality of life was measured by the WHOQOL-OLD scale. With a sample size of 95 elderly people according to the inclusion criteria, namely elderly people aged 60 years and over, healthy elderly people living in nursing homes, elderly people who are still able to communicate. Simple random sampling, a random sampling technique, was used in this procedure. The Sommers'd test was used to obtain data statistically. Results: The level of loneliness in the elderly in the nursing home is on average moderate at 62 elderly (65.3%), the quality of life in the elderly in the nursing home is high at 73 elderly (76.8%). Based on the results of the bivariate analysis, it shows that the level of loneliness with quality of life is negatively and significantly correlated (p = 0.000 and r count = -0.373). Conclusion: This shows that the lower the level of loneliness in the elderly, the higher the quality of life of the elderly.